Secure Cloud Governance Framework - Zbořil, Martin; Svatá, Vlasta, 1952-; Šimeček, Karel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The main target of this thesis is to develop a framework that supports organizations in secure governance of their cloud environment. Besides, this framework might serve also for perform- ing an assessment of the cloud governance posture from the security perspective. The frame- work was developed as a GRC framework since it contains components of Governance, Risk, and Compliance. In the initial phase, a quantitative pre-research in a form of a question- naire was performed to identify the cloud security awareness of Czech organizations. Then, qualitative research in a form of in-depth interviews among cloud security specialists was taken to find specifics and priorities for the framework development. The next step involved a detailed analysis of 10 control catalogs (frameworks, standards, regulations) that contained 1341 controls in total. Based on the retrieved results and findings, the framework for the se- cure governance of the cloud environment was developed. The core of the framework is a list of 170 unique controls. As a secondary target and product, a list of cloud adoption controls that are divided into multiple phases was established. These controls might serve as a guide- line for the cloud adoption process or as a tool for a retrospective assessment of the process. The final output, Secure Cloud Governance Framework, presents a useful contribution to- wards the world of cloud security that distinguishes from an already developed set of controls with the main focus on a cloud service customer, not on a cloud service provider, and with the comprehensiveness of the relevant controls.
Vedoucí práce: Vlasta Svatá
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor disert. práce]; disertace; dissertations